P-selectin promotes neutrophil extracellular trap formation in mice - Etulain, Julia (2015)
Neutrophil extracellular traps(NETs)canbereleased in thevasculature. Inaddition totrapping microbes, they promote inflammatory and thrombotic diseases. Considering that P-selectin induces prothrombotic and proinflammatory signaling, we studied the role of this selectin in NETformation.NETformation(NETosis)wasinducedbythrombin-activated platelets rosetting with neutrophils and was inhibited by anti-P-selectin aptamer or anti-P-selectin glycoprotein ligand-1 (PSGL-1) inhibitory antibody but was not induced by platelets from P-selectin2/2 mice. Moreover, NETosis was also promoted by P-selectinimmunoglobulin fusion protein butnotby control immunoglobulin.We isolatedneutrophils frommice engineered tooverproduce soluble P-selectin (P-selectinDCT/DCT mice). Although the levels of circulating DNA and nucleosomes (indicative of spontaneous NETosis) were normal in these mice, basal neutrophil histone citrullination and presence of P-selectin on circulating neutrophils were elevated. NET formationafter stimulationwithplatelet activatingfactor, ionomycin,orphorbol 12-myristate 13-acetatewassignificantlyenhanced, indicating that the P-selectinDCT/DCT neutrophils were primed for NETosis. In summary, P-selectin, cellular or soluble, through binding to PSGL-1, promotes NETosis, suggesting that this pathway is a potential therapeutic target for NET-related diseases.